KESALAHAN AFIKSASI DALAM PERCAKAPAN SEHARI-HARI MAHASISWA STAI ALI BIN ABI THALIB: ANALISIS MORFOLOGIS - Muhammad Azzam Al Ayyubi; Muhammad Dzaky Dzakir; Agung Pranoto Kadiatmaja (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2026)
This study is motivated by the frequent errors in the use of affixation in students’ daily conversations that do not conform to the rules of the Indonesian language. This study aims to analyze the forms of affixation errors in the daily conversations of students at STAI Ali bin Abi Thalib. This research employs a descriptive qualitative method with a morphological analysis approach. The data were obtained from students’ informal speech through observation and note-taking techniques. The results show that there are errors in the use of prefixes and suffixes, such as the use of non-standard forms influenced by regional dialects, for example “ambek” which should be “mengambil”. These errors are influenced by the students’ regional language background and their lack of understanding of Indonesian morphological rules. This indicates that the use of language that does not conform to standard rules can affect the quality of communication, especially in academic and formal contexts. Therefore, it is necessary to improve students’ understanding of proper affix usage in daily communication.